2017
DOI: 10.1002/pssr.201700366
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ag Schottky Barriers on Be0.02Mg0.26ZnO/ZnO Heterostructures

Abstract: The BeMgZnO/ZnO heterostructures are capable of producing sufficiently high sheet electron densities to allow field effect transistor operation near or at the LO phonon plasmon resonance frequency for minimal LO phonon lifetimes and high electron velocity. Schottky barriers are imperative for the implementation of the aforementioned devices. Therefore, we have undertaken fabrication and characterization of Ag Schottky barriers on Zn-polar Be 0.02 Mg 0.26 ZnO/ZnO heterostructures, exhibiting the said two-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This case may be described by the lateral inhomogeneity of BHs. [23][24][25][26][27][28][29][30] According to GD model, the formed of BH between semiconductor and Schottky contact hasn't homogenous and a mean-BH ECS Journal of Solid State Science and Technology, 2023 12 083010 ( B0 Φ ¯) is defined in Eq. 9a, depending on the standard-deviation S (σ ) of BH.…”
Section: Resultsmentioning
confidence: 99%
“…This case may be described by the lateral inhomogeneity of BHs. [23][24][25][26][27][28][29][30] According to GD model, the formed of BH between semiconductor and Schottky contact hasn't homogenous and a mean-BH ECS Journal of Solid State Science and Technology, 2023 12 083010 ( B0 Φ ¯) is defined in Eq. 9a, depending on the standard-deviation S (σ ) of BH.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to our work 14 , there has been no reports on the investigation of Schottky diodes on BeMgZnO/ZnO heterostructures. Only several studies have reported on Schottky contacts to MgZnO 15 16 , e.g ., with an ideality factor of 2.37, a barrier height of 0.73 eV, and a rectification ratio of only 10 3 15 .…”
Section: Introductionmentioning
confidence: 99%